Using lesson study for teacher development: A case study of Vietnamese EFL teachers’ reflections - Van Thong Nguyen; Trung Cang Nguyen; Bich Nhu Ho (CTU Journal of Innovation and Sustainable Development)
In this article, we present a case study of four Vietnamese teachers of English in a Community College working in a Lesson Study group that prepared them for teacher development in teaching English as a foreign language (EFL). Qualitative data from interview, reflective writing and observation were analyzed during the researched lessons. By conducting Lesson Study, the teachers indicated they were fully aware of the important roles of Lesson Study in their professional development strategies. They declaimed Lesson Study, involving a small group of educators collaboratively designing, teaching, and refining a single lesson could provide a platform for mutual learning, collaboratively designing more effective lesson plans which focus on learning goals, and rendering timid teachers more confident in having their teaching observed by colleagues. However, some constraints faced by the teachers were identified, which may undermine the gains of Lesson Study.